2020
DOI: 10.1007/s11606-019-05592-5
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Preventable Mortality in Hospitalized Patients: a Systematic Review and Meta-analysis

Abstract: BACKGROUND:The number of preventable inpatient deaths in the USA is commonly estimated as between 44,000 and 98,000 deaths annually. Because many inpatient deaths are believed to be preventable, mortality rates are used for quality measures and reimbursement. We aimed to estimate the proportion of inpatient deaths that are preventable. METHODS: A systematic literature search of Medline, Embase, Web of Science, and the Cochrane Library through April 8, 2019, was conducted. We included case series of adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…We authored a systematic review of this literature which found that 3.1% (95% confidence interval [CI], 2.2%-4.1%) of inpatient deaths were preventable, which equates to 22,165 deaths annually (95% CI, 15,730-29,315). 13 If the analysis is limited to patients with greater than 3 months life expectancy, the number is 3575-7150 preventable deaths.…”
Section: Are Estimates Of Death Due To Medical Error Accurate?mentioning
confidence: 99%
See 1 more Smart Citation
“…We authored a systematic review of this literature which found that 3.1% (95% confidence interval [CI], 2.2%-4.1%) of inpatient deaths were preventable, which equates to 22,165 deaths annually (95% CI, 15,730-29,315). 13 If the analysis is limited to patients with greater than 3 months life expectancy, the number is 3575-7150 preventable deaths.…”
Section: Are Estimates Of Death Due To Medical Error Accurate?mentioning
confidence: 99%
“…A much more direct way of measuring deaths due to medical error would be to review inpatient deaths for preventability, rather than the multistage review of admissions. We authored a systematic review of this literature which found that 3.1% (95% confidence interval [CI], 2.2%–4.1%) of inpatient deaths were preventable, which equates to 22,165 deaths annually (95% CI, 15,730–29,315) 13 . If the analysis is limited to patients with greater than 3 months life expectancy, the number is 3575–7150 preventable deaths.…”
Section: Are Estimates Of Death Due To Medical Error Accurate?mentioning
confidence: 99%
“…Iatrogenic complications cause significant morbidity and mortality worldwide. A recent meta-analysis found that approximately 22,165 deaths in hospitalized patients in the United States are preventable each year [ 1 ]. In contrast, an Institute of Medicine report from 2000, “To Err is Human,” attributed roughly 98,000 in-hospital deaths per year to human error [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the 2 decades since the IOM report (2000), the strategies and policy targets to address preventable harm and substandard care by international healthcare organizations appear to have remained ineffective, with patient harm in healthcare deemed as severe or life-threatening [24]. Which as Makary and Daniel, (2016) stated continues to make medical error the third leading cause of death, after cancer and cardiovascular disease [23][24][25].…”
Section: Introductionmentioning
confidence: 99%